Etika Tokoh dalam Kumpulan Cerpen Jawa Pos Edisi Bulan September 2023 - Fahrudin Fahrudin (EDUKASIA: Jurnal Pendidikan dan Pembelajaran, 2024)
Short stories as a form of literary work provide various inspirations and views on life. The various imaginative things that are channeled can then provide various experiences for the reader. The aim of the research is a scientific journal article that analyzes the ethics of the characters in the September 2023 edition of the Jawa Pos short story collection. The method used is qualitative research. The data taken is short stories from the Jawa Pos newspaper in September 2023 and several poems. Next, collect data, analyze, and interpret the data and draw conclusions. The research results show that the data findings obtained are as follows; show respect for others, do not look down on others, behave politely, respect differences of opinion, help others in need. So, in the end, studying short stories can provide life lessons related to ethics.